Keep or Lose It: Mirroring Tana Sangkol in Madura Contemporary Literature - Erika Citra Sari Hartanto (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
Ancestral land or tana sangkol in Madura is a significant material asset possessed by the Madurese people, with attached social and cultural values that link the living and the dead. Massive development on the island, however, has seen people selling their tana sangkol to foreign investors for conversion into shrimp ponds and hotels. This study aimed to analyze tana sangkol’s representation in three short stories, “Anak Cangkul,” “Kutukan Tanah Leluhur,” and “Tanah Warisan,” by Zainul Muttaqin, an author from Sumenep, Madura. The discussion mainly focused on the dramatic contribution of poverty to the sale of tana sangkol to investors, an act that is believed to bring bad luck to the sellers. Furthermore, tana sangkol epitomizes pride to the Madurese people, making them more willing to resist the intrusion of foreign investment. A qualitative research method with a close reading technique was applied and the data were analyzed using the post-colonial ecocriticism theory of Graham Huggan and Helen Tiffin. The results showed that there has been a shift in how the Madurese view their tana sangkol, with them no longer regarding it as sacred ancestral land. Moreover, it is considered to have social and cultural contexts due to its close relationship with the Madurese people’s identity. Meanwhile, the oppression toward farmers is seen as structural and hierarchical.